How to establish workplace learning in long-term care: results from a World Café dialogue - Merel E. A. van Lierop; Judith M. M. Meijers; Erik van Rossum; Johanna E. R. Rutten; Theresa Thoma-Lürken; Sandra M. G. Zwakhalen (BMC, 2022)
Abstract Background As long-term care continues to change, the traditional way of learning for work purposes is no longer sufficient. Long-term care organisations need to become 'learning organisations' and facilitate workplace learning for nursing staff teams. Therefore, insight is needed into what conditions are important for establishing workplace learning. The aim and objective of this article is to gain insight into necessary individual, team and organisational conditions for nursing staff to enhance workplace learning in long-term care settings. Methods This study is a qualitative explorative study. A World Café method was used to host group dialogues in which participants (n = 42) discussed certain questions. Group dialogues were held for the nursing home and community care setting separately due to organisational differences. Nursing staff, experts in workplace learning, educational staff, client representatives and experts in the field of work and organisation in healthcare organisations were invited to a Dutch long-term care organisation to discuss questions of interest. Data were analysed using theme-based content analysis. Results Overall themes concerning individual, team and organisational conditions for workplace learning included: facilitating characteristics (e.g. to be given time and room for [team] development); behavioural characteristics (e.g. an open attitude); context and culture (e.g. feeling safe); cooperation and communication (e.g. giving/receiving feedback); and knowledge and skills (e.g. acquiring knowledge from each other). No major differences were found between settings. Conclusions By assessing the themes at the individual, team and organisational level regarding nursing staff, the current workplace learning situation, and its possible improvements, can be detected.